Research on Labor Market Institutional Environment and Labor Agglomeration—Analysis Based on Dynamic Spatial Panel Data - Guan, Huaping; Zhang, Jianwu; Zhu, Xiaoping (Frontiers in Sociology, 2021)
Institutional environment has a great impact on economic development, but also has a certain impact on labor agglomeration; this paper explains the phenomenon of labor agglomeration from the perspective of labor market institutional environment. Firstly, the paper regards that the labor market institutional environment includes social contract environment and labor contract environment. Secondly, through theoretical analysis, it is considered that a good external institutional environment of the labor market can promote labor agglomeration, and technological progress is also an important factor affecting the agglomeration of highly skilled talents. Thirdly, the paper uses the provincial panel data from 2001 to 2017, to analyze the relevant factors through dynamic spatial Durbin model . Finally, the paper puts forward some policy suggestions to maintain a good institutional environment of the labor market, including: the local government should further improve the labor dispute settlement system, increase the protection of labor rights and interests, and enhance the regional labor market institutional environment.